Cilostazol Protects Against Brain White Matter Damage and Cognitive Impairment in a Rat Model of Chronic Cerebral Hypoperfusion - Terubumi Watanabe; Ning Zhang; Meizi Liu; Ryota Tanaka; Yoshikuni Mizuno; Takao Urabe (2006)
Background and Purpose— White matter lesions contribute to cognitive impairment in poststroke patients. The present study was designed to assess the neuroprotective mechanisms of cilostazol, a potent inhibitor of type III phosphodiesterase, through signaling pathways that lead to activation of transcription factor cAMP-responsive element binding protein (CREB) phosphorylation using rat chronic cerebral hypoperfusion model. Methods— Rats underwent bilateral common carotid artery ligation. They were divided into the cilostazol group (n=80) and the vehicle (control) group (n=80). Performance at the Morris water maze task and immunohistochemistry for 4-hydroxy-2-nonenal (HNE), glutathione- S -transferase-pi (GST-pi), ionized calcium-binding adaptor molecule 1, phosphorylated CREB (p-CREB), Bcl-2, and cyclooxygenase-2 (COX-2) were analyzed at baseline and at 3, 7, 14, 21, and 28 days after hypoperfusion. Result— Cilostazol significantly improved spatial learning memory (6.8±2.3 seconds; P <0.05) at 7 days after hypoperfusion. Cilostazol markedly suppressed accumulation of HNE-modified protein and loss of GST-pi–positive oligodendrocytes in the cerebral white matter during the early period after hypoperfusion ( P <0.05). Cilostazol upregulated p-CREB and Bcl-2 ( P <0.05), increased COX-2 expression, and reduced microglial activation in the early period of hypoperfusion. Conclusion— Our results indicate that cilostazol exerts a brain-protective effect through the CREB phosphorylation pathway leading to upregulation of Bcl-2 and COX-2 expressions and suggest that cilostazol is potentially useful for the treatment of cognitive impairment in poststroke patients.